Study on macroeconomic factors that influence unemployment rate in Malaysia / Tunku Aimi Diyana Tunku Abdul Hamid (Faculty of Business and Management, 2017)
This study sought to explores the determinant factors affecting unemployment rate in Malaysia over the period of 1985 until 2015. The data series of variable Inflation Rate (CPI), Oil Price Volatility (CPO), Exchange Rate (ER) are to measure their relationship with Unemployment Rate (UR) using time series analysis. Moreover, this study attempts to examine the best model using Multiple Linear Regressions (MLR). The findings indicate that there is a significant negative relationship between Inflation Rate (CPI) and Unemployment Rate (UR). There is also a significant positive relationship between Oil Price Volatility(CPO) and Unemployment Rate (UR). However, study indicates that relationship between Exchange Rate (ER) and Unemployment Rate are insignificant positive relationship.